SUNAT PEREMPUAN: CERMIN BANGUNAN SOSIAL SEKSUALITAS MASYARAKAT YOGYAKARTA DAN MADURA - Basilica Dyah Putranti (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2005)
The objective of the study is to comprehend how the practice of Pemale Genital Cutting (PGC), or 'sunat perempuan' in local term, reflects a social contruction of sexuality in Indonesia society, and how it relates to sexual and reproductive health. The study was conducted during 2002 in Yogyakarta and Madura, considering that both areas have distinct sociocultural contexts.The study reveals that PGC, as MGC, is socially meant 'to Islamize' member of society. The male religious leaders' dominance and rigid interpretations of Islamic holy books may be conducive for male-biased sexual behaviors and harmfulprocedures of PGC among Madurese. Among Javanese, by contrast, PGC is known as a part of court tradition, to be connected with a puberty rite which articulates symbolic actions. As opened social discourse is more accepted among Javanese, PGC is easily forgotten. Nonetheless, the meaning of PGC as a puberty rite has served as a basis for gender divisions among Javanese todays.